Pengaruh ICG, Profitability, dan CSR Terhadap Islamic Sustainability Report Discloure pada Jakarta Islamic Index - Salsabila, Aina; Hafizh, Muhammad (Program Studi Manajemen Keuangan Syariah, 2025)
The aim of this research is to examine how the Islamic Sustainability Report (ISR) of Jakarta Islamic Index Companies for the 2019–2024 timeframe is impacted by Islamic Corporate Governance (ICG), profitability (ROA), and corporate social responsibility (CSR). The research data used in this study is quantitative, and it employs a descriptive statistical approach. Purposive sampling was used to gather data from a population of 30 Jakarta Islamic Index (JII) enterprises. This resulted in a sample of 10 JII companies, totaling 60 observations. Panel Data Regression with the Fixed Effect Model in EViews 12 was used to analyze the data. The results showed that partially only ICG and ROA showed a significant positive effect while CSR did not have a significant positive effect on ISR. However, simultaneously ICG, ROA, and CSR had a positive and significant effect on ISR. An R2 of 0.4322, or 43.22%, illustrates the analytical capability of the model. The three independent variables explain the variation in ISR. These findings underline how crucial it is to apply sharia-compliant corporate governance to attain strong financial results and promote the release of sustainability reports that are based on sharia.